Análise de polimorfismos dos genes codificadores da catecol-o-metiltransferase (COMT) e guanosina trifosfato ciclohidrolase 1 (GCH1) em pacientes com neuralgia do trigêmeo - João Gabriel de Azevedo José Romero (2020)
Trigeminal neuralgia (NT) is characterized by paroxysms of severe shock-like pain within the distribution of one or more divisions of the trigeminal nerve. Genetic polymorphisms in genes encoding catechol-o-methyltransferase (COMT) and guanosine triphosphate cyclohydrolase (GCH1) were associated with increased susceptibility and protection to painful diseases, respectively. This work evaluated rs4680 (COMT) and rs8007267 (GCH1) genetic polymorphisms in patients diagnosed with NT. Forty-eight individuals with NT, whose clinical evaluation of pain was previously performed, and 48 controls were submitted to collection of biological material by oral swabs and DNA was analyzed by real-time polymerase chain reaction with specific probes (Taqman assay). Results showed no association among COMT or GCH1 polymorphisms and the presence of TN. Genotype distribution and allele frequencies did not correlate to pain severity. Although no association of evaluated polymorphisms and trigeminal neuralgia or pain was observed, our data contributes to the knowledge of genetic susceptibility to trigeminal neuralgia, which is very scarce.